2016
DOI: 10.1051/0004-6361/201628300
|View full text |Cite
|
Sign up to set email alerts
|

MESA meets MURaM

Abstract: Context. Space-based observations of solar-like oscillators have identified large numbers of stars in which many individual mode frequencies can be precisely measured. However, current stellar models predict oscillation frequencies that are systematically affected by simplified modelling of the near-surface layers. Aims. We use three-dimensional radiation hydrodynamics simulations to better model the near-surface equilibrium structure of dwarfs with spectral types F3, G2, K0 and K5, and examine the differences… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(84 citation statements)
references
References 41 publications
(60 reference statements)
2
82
0
Order By: Relevance
“…These ratios are useful for model fitting, where they can be used instead of individual frequencies (Lebreton & Goupil 2014;Silva Aguirre et al 2015) because they are largely insensitive to the stellar surface layers (Kjeldsen et al 2008a;Ball & Gizon 2014;Roxburgh 2015;Ball et al 2016). For further details on the use of these ratios we refer to Roxburgh & Vorontsov (2003, Roxburgh (2005), Otí Floranes et al (2005), and Silva Aguirre et al (2011,2013).…”
Section: Quality Assurancementioning
confidence: 99%
“…These ratios are useful for model fitting, where they can be used instead of individual frequencies (Lebreton & Goupil 2014;Silva Aguirre et al 2015) because they are largely insensitive to the stellar surface layers (Kjeldsen et al 2008a;Ball & Gizon 2014;Roxburgh 2015;Ball et al 2016). For further details on the use of these ratios we refer to Roxburgh & Vorontsov (2003, Roxburgh (2005), Otí Floranes et al (2005), and Silva Aguirre et al (2011,2013).…”
Section: Quality Assurancementioning
confidence: 99%
“…The comparison between hydrodynamical simulations and stellar models (Ball et al 2016) suggested an increasing surface term for dwarfs from the spectral type of K5 to F3. Trampedach et al (2017) estimated the frequency shifts in various types of stars with a grid of convection simulations and also gave a clear correlation between the surface term and atmospheric parameters.…”
Section: The Surface Term In Evolved Starsmentioning
confidence: 98%
“…see Sonoi et al 2015;Ball et al 2016), and by trying to mitigate surface effects when comparing models and observations. In this respect a way forward would be to determine the star's mean density by using the full set of observed acoustic modes, not just their average frequency spacing.…”
Section: Surface Effectsmentioning
confidence: 99%